ADSORPTION AND DOWNWARD MOVEMENT OF LINDANE IN ORGANIC MATTER RICH SANDY LOAM SOIL OF UTTARANCHAL, INDIA - SINGH, SANJAY KUMAR; P. RAHA; H. BANERJEE; S. K. SINGH (The Bioscan, 2013)
The effect of soil properties on the adsorption, movement and distribution of Lindane in soils of Uttaranchal, India was studied. The results indicated that soils with different physico-chemical properties have different effects on the adsorption, movement and distribution of pesticide, especially at higher concentration levels. Two composite soil samples were collected that having diversified phycio-chemical properties were analyzed. The Adsorption of Lindane to soils was best found to fit a Freundlich equation and Freundlich’s adsorption constant ‘K’ and ‘1/n’ values were in the range of 0.941 and 0.995 respectively. The highest Kd value (21.24) was received to the Almora soil followed by Udham Singh Nagar soil (20.24) with a high clay content and organic matter content exhibit the high adsorption capacity. In the present study, Lindane downward movement was performed in the packed soil column; the distribution of Lindane was obtained throughout the column and even showed presence in the lower most soil core. The recovered amount of Lindane was detected on Almora (75.38%) followed by Udham Singh Nagar (74.76%) in 0-10cm depth. It was noted that the relatively high organic matter content and clay content of soil restricted the leaching of the soil.